Helicobacter pullorum among Poultry in Assiut-Egypt: Genetic Characterization, Virulence and MIC - Mohamed, Moemen A.; Ibrahim, Ragab S.; Shahata, Moustafa A.; El-Refaie, El-Refaie M. (International Journal of Poultry Science, 2010)
The molecular characterization, the MICs of antibiotics (with clinical relevance in human and veterinary medicine) for the selected isolates of H. pullorum and its Pathogenicity to chickens were carried out. A total of 1800 samples (cloacal swabs, cecal contents and liver) were collected from chickens, turkeys and ducks. H. pullorum could be identified only from chickens with a percentage 39.33%. One hundred isolates were identified as H. pullorum by phenotypic tests. Those were subjected to Polymerase Chain Reaction (PCR) assay based on 16S rRNA to confirm phenotypic identification. These results revealed 100% accordance between phenotypic and genotypic identification and a considerably shortened analysis time, provides a sensitive and rapid alternative for applications in the identification of H. pullorum and highlights the potential of PCR technology in routine pathogens identification. The prevalence of cdtB gene was analyzed among the examined H. pullorum strains (n = 100) using PCR assay. The cdtB gene was present in nearly from 79 H. pullorum strains out of 100 examined ones. Fifty-three out of the 79 cdtb positive strains (67%) were obtained from diseased birds. In contrast to 26 out of 79 positive cdtB gene strains (32.9%) could be obtained from clinically healthy chickens. This different distribution of genetic virulence markers between isolates may indicate that gene may play a role in the pathogenesis of this organism to chickens. Infection was induced in 39 healthy one-day-old chicks with isolated H. pullorum strain by oral route. The mean incubation time was 96 h. Considerable weight loss was observed in the experimental group compared with the control group. Diarrhea observed in chicks from the 5th day post infection. Postmortem revealed unabsorbed yolk sac and distended ceca. The susceptibilities of Helicobacter pullorum (20 strains) to 6 antimicrobial agents were investigated by determination of the MIC using the Micr-broth dilution method. All examined strains were resistant to ciprofloxacin, gentamicin and erythromycin followed by tetracycline (70%) and complete susceptibility to colistin and ampicillin, indicating the possibility of chicken being a source of the resistance tool for humans.